2022
DOI: 10.1037/drm0000193
|View full text |Cite
|
Sign up to set email alerts
|

A presleep consideration of an intrusive thought enhances the possibility of dreaming of it.

Abstract: This study investigated whether focusing on an intrusive thought before sleeping led to an increased likelihood of dreaming of the thought. A total of 150 participants were randomly assigned to three different kinds of conditions: an expression condition (focus on an intrusive thought for 5 min before sleeping), a suppression condition (suppress an intrusive thought for 5 min before sleeping), and a control condition (think about anything for 5 min before sleeping). Also, they completed a dream diary upon waki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Yet in Wang et al 's (2022) study, the self-rating method did not find the dream rebound effect, whereas the external-rating method did. The inconsistent results between Wegner et al (2004) and Wang et al (2022) implied that the external-rating method was more suitable for group comparisons. Yet still, there was a need for more research to explore this idea.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Yet in Wang et al 's (2022) study, the self-rating method did not find the dream rebound effect, whereas the external-rating method did. The inconsistent results between Wegner et al (2004) and Wang et al (2022) implied that the external-rating method was more suitable for group comparisons. Yet still, there was a need for more research to explore this idea.…”
Section: Introductionmentioning
confidence: 92%
“…To our knowledge, most of this kind of evidence was correlational in nature, because there was a difficulty to manipulate dream content directly (for a talk, see Schredl, 2003 ). Yet still some studies showed a causal relationship for this topic (e.g., Nikles et al, 1998 ; Wegner et al, 2004 ; Taylor and Bryant, 2007 ; Kröner-Borowik et al, 2013 ; Malinowski et al, 2019 ; Feng and Wang, 2022 ; Wang et al, 2022 ). These studies can be divided into two kinds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, thought suppression is also related to poorer sleep quality [ 18 , 19 ]. Intrusive thoughts, whether suppressed or focused upon, are also followed by more negatively toned dreams [ 20 ]; that is, pre-sleep rumination also affects dreams in a negative way [ 21 ]. Taken together, these empirical data would predict that dysfunctional sleep-related metacognitions are associated with negatively toned dreams.…”
Section: Introductionmentioning
confidence: 99%